A nested polymerase chain reaction (nPCR) based assay for sensitive detection of latent Trypanosoma evansi infection in water buffaloes - SUDAN, VIKRANT; JAISWAL, AMIT KUMAR; PARASHAR, RAHUL; SHANKER, DAYA (The Indian Journal of Animal Sciences, 2014)
A nested polymerase chain reaction (nPCR)-based assay was developed and evaluated for rapid detection of latent and cryptic cases of Trypanosoma evansi in buffaloes. Four oligonucleotide primers (TE1, TE2, TE3 and TE4), selected from nuclear repetitive gene of T. evansi, were designed and used for PCR amplifications. The first amplification, using a pair of outer primers TE1 and TE2, produced a 821– bp primary PCR product from T. evansi DNA. The second amplification, using nested (internal) pair of primers TE3 and TE4, produced a 270–bp PCR product. The nested primers TE3 and TE4 increased the sensitivity of the PCR assay and as little as 10 fg of T. evansi DNA (equivalent to a single copy of the putative gene of the parasite) was amplified and visualized onto ethidium bromide-stained agarose gels. Amplification products were not detected when the PCR-based assay was applied to DNA from other blood parasites including Thieleria annulata and Babesia bigemina. The described nPCR-based assay provides a valuable tool to study the epidemiology of T. evansi infection in buffaloes and other susceptible animal populations.